Allegro de concierto, capricho español: and other works for solo piano - Granados Campiña, Enrique. 1867-1916 (Dover classical music for keyboard, 2002)
Full of the color, harmonies, and rhytms of Spanish folk music, the captivating piano works of Enrique Granados have influenced later composers and spread the Spanish style throughtout the world.